Penerapan Pendekatan Aptitude Treatment Interaction dalam Pembelajaran Fiqih di Kelas VII MTS NW Selebung Ketangga Kecamatan Keruak Kabupaten LOTIM - Saprudin Efendi (ISLAMIKA, 2019)
This study discusses the application of the ATI learning model in Fiqh learning at MTs NW Selebung Ketangga 2018/2019 academic year. By taking research subjects in class VII B, taking this class who have serious problems, namely low activity and learning achievement Fiqh. The method used in data collection is the method of observation and testing. While the analysis techniques used are descriptive statistical techniques and quantitative analysis. The results showed that the application of ATI learning also improved the quality of Fiqh student achievement. This increase consists of an increase in the number of students studying classically and individually. Classically the increase in the percentage of students' mastery learning is 39%, from the initial data 45% to 84%. Classically, all students in the class have met the classical graduation standard, that is if the class has reached a value equal to 65 or more than a minimum of 80%. While the individual completeness is all students except 6 people out of 25 students have reached values above 65.